The Influence of Revisit Intention Through E-WOM and City Branding in The Creative Tourism of The Ngarsopuro Night Market - Fadila, Sarah (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Various studies mention that tourists are currently changing their tourism travel patterns from buying products to buying experiences. From mass tourism to responsible tourism. Responding to changes in consumer / tourist demand from buying products to buying experiences and the growing need for responsible tourism, in terms of tourism, what is known as creativity-based tourism or creative tourism has emerged. Along with the development of tourism, especially cultural tourism, which not only places tourists as "spectators" or connoisseurs, but they then change their goals to try to understand the local culture. To determine the effect of E-WOM on the intention to revisit the Ngarsopuro Night Market creative tourism. To determine the effect of City Branding on the intention to visit Ngarsopuro Night Market creative tourism. To find out eWOM and City Branding together have an effect on the intention to visit Ngarsopuro Night Market creative tourism The method in this study is a quantitative method. The data collection method uses a questionnaire. While data analysis uses Path Analysis Test. The results of this study indicate that: 1) There is a positive and significant effect of E- WOM on revisit intention, so the first hypothesis is accepted. 2) There is a positive and significant effect of City Branding on revisit intention, so the second hypothesis is accepted. 3) There is a positive and significant effect of E-WOM and City Branding on return visit intention, so the third hypothesis is accepted.